A DAY OUT WITH FOREIGNER: AN EFFORT TO IMPROVE STUDENT’S CONFIDENCE IN COMMUNICATING IN ENGLISH - Eka Grana Aristyana Dewi; A.A.Gede Adi Mega Putra (Universitas Muhammadiyah Makassar, 2025)
English proficiency is an essential skill in the professional world, facilitating access to global information and career advancement. The National Association of Colleges and Employers (NACE, 2024) identifies communication skills as a key component of employability. However, many Indonesian students, including those at a technology-based university in Bali, struggle with low confidence in speaking English. The previous study found that factors such as fear of making mistakes, lack of speaking practice, limited vocabulary, and negative past experiences contribute to this challenge (Dewi, 2024). This study examines the effectiveness of the “A Day Out with a Foreigner” program, which applies Project-Based Learning (PBL) based on Experiential Learning Theory (ELT) to enhance students’ confidence in speaking English. A quantitative associative research design was employed, with data collected through pre-test and post-test questionnaires. The sample consisted of 79 students, selected from a population of 90 using random sampling based on the Henry King Nomogram. Data were analyzed using the Spearman Rank correlation test, a non-parametric inferential statistical method. The results indicate a strong positive correlation between pre-test and post-test scores (Rs = 0.862), demonstrating that the program effectively boosts students’ confidence in spoken English.